DIVERSITY OF BRYOPHYTA IN THE DEWI SILA WATERFALL AREA, KETAMBE VILLAGE, KETAMBE DISTRICT, ACEH SOUTHEAST ACEH REGENCY AS A MEDIA FOR LEARNING BOTANICAL PLANTS - Nursafiah Nursafiah; Muhammad Yassir; Rika Aswarita; Lidiya Cahaya (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
Diversity is the combination of the number of species and the number of individuals in one community. Moss is a plant that is classified as a low level because it cannot be distinguished between its roots, stems and leaves. The purpose of this research is to; knowing the types of moss plants found in Dewi Sila Ketambe Waterfall; Knowing the level of diversity of moss plants in Dwi Sila Ketambe Waterfall; and to find out the utilization of research results on the diversity of mosses in the Dwi Sila Ketambe Waterfall as a practical reference for the subject of Lower Plant Botany. The research design used to obtain field data, namely by using the roaming method, exploring or observing at the observation site. Sampling was taken by purposive sampling at Dwi Sila Ketambe Waterfall. The research location was divided into 3 observation zones and each observation point consisted of 1 transect line and 5 plots measuring 5mx5m for each transect line. The results of the study show that there are 13 species of moss plants consisting of 8 families. The diversity of moss plants in Dwi Sila Ketambe Waterfall is classified as moderate with a diversity index of ? = 2.366. The conclusions of this study are: 1) The types of Moss plants found in Dwi Sila Ketambe Waterfall consist of 13 species from 8 families, Arthoniaceae, Calymperaceae, Brachytheciaceae, Hypnaceae, Fissidentaceae, Pottiaceae, dan Machatiaceae; 2) The diversity of Moss Plant Species found in Air Dwi Sila Ketambe is classified as moderate; 3) The results of this study are utilized in the form of a pocket book and herbarium.Keywords: Diversity, Bryophyta, Learning Media.